Twenty years' monitoring of a population of Italian crested newts Triturus carnifex: strong site fidelity and shifting population structure in response to restoration. Issue 5 (3rd September 2017) - Mori, Emiliano; Menchetti, Mattia; Cantini, Matteo; Bruni, Giacomo; Santini, Giacomo; Bertolino, Sandro
Abstract : Human-induced environmental alterations, e.g. the introduction of alien species and the application of management practices, together with climatic change, represent the main threat to worldwide amphibian conservation. Long-term monitoring programmes are mandatory to monitor the status of amphibian populations in changing landscapes and climatic conditions. In this study, we showed the population dynamic of the Italian crested newts Triturus carnifex living in four artificial ponds in Central Italy over a 20-year period. Adult newts were recognised through a capture-mark-recapture protocol, involving the analysis of belly patterns. The first best population model showed a constant newt survival among years and a complete recapture rate; the second supported model showed a sex-dependent survival, with slightly higher values for males with respect to females, and corroborated a complete recapture rate. A high philopatry occurred: we observed less than 10% of individuals dispersing from a birth site to other ponds. In 20 years of continuous monitoring, the population of Italian crested newt increased. The removal of goldfish Carassius auratus from one of the ponds in 2010 allowed adult newts to overwinter within the pond and to have two reproductive periods, with overwintering larvae after the second spawning.